Territory, Landscapes, and Actors: A Public Policy Approach to the Planning of the Riverfront in Paraná, Entre Ríos. (Res Gesta, 2025)
This study focuses on the riparian landscape —both natural and cultural— within public land-use planning policies in Paraná, Entre Ríos. It examines the complex relationship between landscape, heritage, and stakeholders along the northern riverfront, from Bajada Grande to the El Yeso stream, with particular attention to Puerto Nuevo and Puerto Viejo, areas that preserve the city’s tangible and intangible memory. The research identifies key social, territorial, environmental, and cultural issues affecting these landscapes and their connection to land-use policies. It offers an initial theoretical and methodological reflection aimed at integrating stakeholders, their institutions, and logics into territorial planning through a landscape-centered approach.
Keywords: Landscape; Cultural and natural heritage; Stakeholders; Public land-use planning policies